Sid Caesar papers - Caesar, Sid, 1922-
Chiefly annotated working scripts for "Your Show of Shows"(1950-1954), the television series in which Caesar appeared with Imogene Coca, Howard Morris, and Carl Reiner; and scripts and production files for "Caesar's Hour" (1955-1957), the series in which he appeared with Janet Blair, Nanette Fabray, and Morris and Reiner. Writers represented include Mel Brooks, Selma Diamond, Larry Gelbart, Lucille Kallen, Sheldon Keller, Neil Simon, Michael Stewart, and Mel Tolkin.
Actor and comedian.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Blair, Janet; Brooks, Mel, -- 1926-; Coca, Imogene; Diamond, Selma; Fabray, Nanette; Gelbart, Larry; Kallen, Lucille; Keller, Sheldon; Morris, Howard, -- 1919-; Reiner, Carl, -- 1922-; Simon, Neil; Stewart, Michael, -- 1929-1987.; Tolkin, Mel; Caesar's hour (Television program); Your show of shows (Television program); Television -- Production and direction; Television scripts; Actors; Comedians